Tinjauan Yuridis Terhadap Perjanjian Pekerjaan Optimalisasi Sistem Pengembangan Air Minum Ibu Kota Kecamatan Siantar Narumonda Kabupaten Toba Samosir (Studi Pada PT. Nugraha Tyaga Supala) - Olivia Napitupulu; Rafiqi Rafiqi; Windy Sri Wahyuni (Universitas Medan Area, 2019)
District Government Toba Samosir as an effort to optimize the drinking water development system in the region is carrying out the work of optimizing the drinking water supply system. In the agreement that acts as the employer is the official making commitment for the development of drinking water and sanitation in North Sumatra province in collaboration with PT. Nugraha Tyga Supala who acted as a contractor. The research method is normative juridical namely by reviewing document studies and conducting studies at PT Nugraha Tyaga Supala and conducting interviews with related parties. The procedure for implementing the contract of employment is in accordance with the provisions of the applicable law starting with the planning stage in advance, then the public tender process is carried out with the post-qualification method and the cover one method through an announcement by the employer. The rights and obligations of each commitment official namely the right to supervise and inspect the work and are obliged to pay for the work in accordance with the agreement in the contract, while the provider has the right to receive payment according to the contract value stated and is obliged to complete the work on the date in the contract and is responsible during the maintenance period.